Regulation of Biobanks in Italy - Cannovo, Nunzia; Cingolani, Mariano; Guarino, Rosa; Fedeli, Piergiorgio (Frontiers in Pediatrics, 2020)
In Italy, a biobank is “a non-profit organization that must be officially recognized by the appropriate healthcare authority in the member states and must guarantee the treatment, distribution and conservation of biological material according to standards of quality and professionalism,” but must not conserve material already regulated by specific laws, as is the case for organs for transplants, blood for transfusions, as well as embryos and gametes for medically assisted reproduction. The concept of biobank includes not only biological samples, but also the related database of clinical and personal information, from which the subject's lifestyle can be deduced. Unfortunately, at the moment, Italian law does not offer specific itineraries for achieving this legal status.